Sun Tzu and the Art of Modern Warfare - McNeilly, Mark R.
1 online resource (329 pages)
Keywords: Mark McNeilly has extracted from Sun Tzu's The Art of War the six concepts most applicable to modern warfare, making them easy to understand and apply to military situations. Drawing on a wealth of fascinating historical examples, McNeilly shows how these six principles might be used in modern wars and how they can provide insight into current affairs, such as the war on terrorism and China's increasingly important strategic and military role in the world. This updated edition reflects on all that has happened in the past ten years, including the wars in Iraq and Afghanistan, the challenge of Iran, the “Arab Spring“, and the continued rise of China.